Outcome of patients with liposarcoma: A retrospective review over 12 ​Years in a single center - Teck Liang Tie; Suryasmi Duski (Clinical Surgical Oncology)
Background: Liposarcoma is the most common soft tissue sarcoma, which comprises around 20% of soft tissue sarcoma. While diverse therapeutic approaches exist for liposarcoma, the primary goal remains the achievement of effective local disease control. Wide resection of liposarcoma is the cornerstone of treatment. Radiotherapy is often employed as an adjuvant measure to enhance the local disease control. At Hospital Kuala Lumpur, the treatment protocol includes R0 resection and followed by adjuvant radiotherapy. This study aims to review the demographic characteristic of liposarcoma patients and evaluate the efficacy of their treatment based on the treatment protocol. Method and material: This is a retrospective cohort study. A total of 72 patients (male/female ​= ​43/29) were included in this study. Recorded parameters included the histologic subtype, tumor location, treatment modality, resection margin, radiotherapy status, and occurrences of local recurrence and metastasis. Result: Histopathological examination revealed a varied spectrum of liposarcoma subtypes, with the predominant subtype being atypical lipomatous tumor (n ​= ​35), followed by myxoid liposarcoma (n ​= ​32), two cases of dedifferentiated liposarcoma, and three cases of pleomorphic liposarcoma. Of these patients, 69 underwent resection, while three necessitated amputations. Total 62 achieving negative and 10 cases had R1 margins. Adjuvant radiotherapy was administered in 58 cases. Overall, the local recurrence was observed in only six cases. Conclusion: This study emphasizes that achieving R0 resection is the fundamental approach in the treatment of liposarcoma and is able to minimize the risk of local recurrence.